Elevated Levels of Plasma Superoxide Dismutases 1 and 2 in Patients with Coronary Artery Disease. (17th October 2016) - Peng, Ji-Ren; Lu, Ting-Ting; Chang, Hao-Teng; Ge, Xuan; Huang, Bian; Li, Wei-Min
Abstract : Aims . To measure plasma levels of superoxide dismutases 1, 2, and 3 (SOD1, 2, 3) and determine whether SODs can function as biomarkers for coronary artery disease (CAD). Patients & Methods . Patient groups were as follows: patients with stable angina pectoris (SAP, n = 33 ), patients with acute coronary syndrome (ACS, n = 49 ), and controls (n = 42 ). Protein quantification was done using ELISA. Results . The concentrations of plasma SOD1 and SOD2 were higher in CAD than in healthy controls. No difference in SOD3 levels between CAD and control groups was found. Limited correlations were found between SODs and gender, age, and severity of coronary artery stenosis. Conclusions . Plasma levels of SOD1 and SOD2 were elevated in patients with CAD and might serve as surrogate biomarkers for CAD.